Reactions of banana plantlets Musa acuminata L. to extracellular polysaccharides from Ralstonia zyzygii subsp. celebensis causal agent of blood diseases. Issue 1 (April 2020) - Baharuddin,; Ulfa, F; Eryuni,
Abstract: Extracellular polysaccharides generated by bacteria play an important role in inhibiting the translocation of nutrients and water, protecting bacteria in extreme conditions and neutralizing compounds released by plants. Giving filtrate pathogens with different concentrations causes different plant reactions in each variety. This study was aimed to determine the effect of various concentrations of extracellular polysaccharides (EPS) obtained from Ralstonia zyzygii subsp celebensis (rzc) towards the growth of banana plantlets in-vivo. A randomized complete design was used with parameters of two varieties (Barangan and Ambon) and EPS in different concentration of 0; 10; 11.5; 13, and 14.5%. EPS filtrate culture was obtained from initially growing bacteria on NGA (Nutrient Glucose Agar) medium and subculture (mineral media) and centrifuged at 6000 rpm for 15 minutes then sterilized with a membrane filter. Extracellular polysaccharides were put into MS media, then planting 3-month-old banana plantlets with uniform growth. Culture were placed for inoculation that controlled in a culture room at a temperature 26 ± 2 0 C with relative humidity of 55 ± 5% and were exposed to 16 h photo period. Observation parameters were number of shoots and leaves, time of appearance of shoots and leaves (days). The results showed that response of Barangan gave better results on number of shoots than ambon in tolerating the effect of extracellular polysaccharides filtrate. Concentration of 13% is tolerance limit for the growth number of banana plantlets. Barangan variety can produce the highest number of shoots at a concentration of 13% extracellular polysaccharides filtrate.